Guidance to implementing evidence-based initiatives to manage pandemics in healthcare services: a discussion paper. Issue 4 (22nd December 2020) - Khalil, Hanan; Liang, Zhanming; Karimi, Leila; Ferrier, J. Adamm; Leggat, Sandra G.
Abstract : ABSTRACT: Planning and implementing surge capacity in healthcare services is challenging. The evolving nature of viral transmission makes it difficult to predict the potential impact on the health system and the readiness of healthcare managers and professional staff in responding to system transformation and consequential impacts. This is compounded by sudden increased demands in the types of work required. Guidance for implementing targeted strategies for health systems and services should include evidence that considers the feasibility, appropriateness, meaningfulness and effectiveness of healthcare practices at both the system and organization level. This is consistent with the Joanna Briggs Institute (JBI) model of evidence synthesis and translation. Evidence-based decision-making is a core management competency for health service leadership and the mechanism for improving the quality of management decisions, and hence better service delivery, effectiveness and efficiency. Human resources are the most important asset in crisis management. Health managers must create responsive surge capacity by quantifying existent human and material resources and the shortfall needs required to meet anticipated additional demand. We believe a multifaceted approach is the key to developing systemic surge capacity within the heath sector when faced with the management of crises such as pandemics. We explore and discuss the desirability of strategies based on the JBI model of evidence synthesis and implementation with a view to encouraging the creation of registries and follow-up systems. We believe this will encourage the effective use of human resources including the upskilling in how future crises may be addressed.